A mediação da biblioterapia por bibliotecários em ambiente hospitalar: relatos do projeto de extensão “Turma da Leitura" - SILVA, Osimara da Silva e (2021)
It is admitted biblioterapia for the use of the reading as therapeutical tool. This work is characterized for answering the following question “as to the use of the bibliotera-sink through the project Group of the reading it contributed with the children and adolescents hospitalized in Infantile the Oncológico Hospital of Belém”. Of this form, they are had co me the general objective to evaluate the contribution and the results of the application of the Biblioterapia in oncológicos patients. Moreover, in relation to the specific objectives, that is, to investigate the biblioterapia as therapeutical effect and to argue its effectiveness while incentive to practical of the reading in the Project the Group of the Reading, to identify to the results of the interaction of the application of the Biblioterapia for the volunteers of the project Group of the Reading to the oncológicos patients of Infantile the Oncológico Hospital of the city of Belém by means of the research-action. Being thus, it argued concerning the mediation of the reading carried through for librarians, basing itself on the bibliographical research of the scholars of the thematic one, as well as the librarian as mediating of the information. Therefore, stories of the extension project had been used Group of the Reading, beyond the used biblioterapêuticos components during its execution. The adopted methodology is characterized for the descriptive research, using the research-action for collection of - of and the analysis of the results from the comments registered in fiches. Finally, with this it was possible to conclude the results and the contribution of the results of the reading through the biblioterapia for children and carrying adolescents of cancer attended by the project.